CLAIMANT MEDICINAL PLANTS IN MANAGEMENT OF STRETCH MARKS: A REVIEW ROOTED ON CLINICAL EVIDENCES - Bhavya Agarwal1, Parkhi Rastogi*1, Virender Pal Kaur2, Urvashi Sharma2, Mayank Tyagi3, Divyansh Dutt Kaushik3, Karina Chaudhary4,Vikrant Verma3 (Chelonian Research Foundation, 2023)
Striae distensae (striae) are cutaneous lesions that have gravely troubled the mental health and quality of life. Conventional therapies are being used to manage and prevent stretch marks. However, these therapies are not entirely effective and no one has been reported to have fully reversed the striae and recovered the normal appearance of skin. Worldwide, numerous medicinal plants were utilized for preventing striae distensae due to presence of great chemical components in various ancient system of medicine. Medicinal plants with anti-stretch mark property are being more desired, owing to more potency and effectiveness. The review focuses on various plants that have been reported to be effective in reducing and preventing stretch marks. This includes Centella asiatica, Aloe vera, Croton lechleri, Rubia cardifolia, Curcuma domestica, Lagerstroemia indica, Chrysopogon zizanioides, Olea europaea etc. All of them have shown a certain degree of anti-stretch mark activity by different mechanism of action. Key Words: Striae distensae, striae rubrae, striae albae